The Growth of Titi Plant (Gmelina moluccana) and Environmental Factors that Affect It - Yulen Melaira; Febian Filiph Tetelay; Hendrik S E S Aponno (Jurnal Agrosilvopasture-Tech, 2023)
Gmelina moluccana is an Indonesian species of flowering plant native to eastern Indonesia, especially the Moluccas and New Guinea. The people of Maluku widely use this type of wood to make lightweight building materials and boats because it is light and durable. In addition, parts of this species are used as traditional medicine by the community. This study aimed to determine the rate of increase in diameter and height of Titi (Gmelina moluccana) 9 years after planting and to determine the factors that affect the growth of Titi (Gmelina moluccana) 9 years after planting. The method used in this study is a quantitative descriptive method to measure the current annual increment (CAI) and mean annual increment (MAI), followed by a simple linear regression analysis to determine the effect of environmental factors on growth. CAI average nine years diameter 2.51 cm/year, height 1.53 m/year, MAI average nine years diameter 1.94 cm/year, height 1.15 m/year. Environmental factors affecting Titi's growth include soil pH and soil moisture.